The rs5918 polymorphism in the ITGB3 gene increases the risk for preeclampsia in pregnant women with fetal growth retardation - Oleg V. Golovchenko; Irina V. Ponomarenko; Mikhail I. Churnosov (IP Berlin A.V., 2021)
Aim. To assess the relationship of rs5918 ITGB3, rs1126643 ITGA2 and rs5985 F13A1 polymorphic loci with the risk for preeclampsia (PE) in pregnant women with fetal growth retardation (FGR). Materials and methods. The study included 272 pregnant women, of which 76 had a combination of PE and FGR and 196 had FGR. In the studied groups, genetic testing was carried out for three polymorphic loci of candidate genes for hereditary thrombophilia (rs5918 ITGB3, rs1126643 ITGA2, and rs5985 F13A1). Results. The rs5918 genetic variant in the ITGB3 gene is associated with the development of PE in pregnant women with FGR: C allele of rs5918 ITGB3 increases the risk for this complication of pregnancy by 1,8 times (OR 1.761.77, p0.036, pperm0.038). The rs5918 polymorphism determines an increase in the affinity of DNA motifs for seven transcription factors (BDP1, ELF1, IRF, NRSF, Pax-5, Sp1, and Zfx), is a missense mutation and causes the Leu59Pro amino acid substitution in the 3 subunit of integrin, is multidirectionally associated with the expression of five genes (EFCAB13, TBKBP1, NPEPPS, MRPL45P2, THCAT158) and alternative splicing of two genes (EFCAB13, MRPL45P2), is located in the region of functionally important DNA regions (promoters and enhancers) in cell cultures and organs which are pathogenetically important for the formation of PE and FGR. Conclusion. The rs5918 polymorphism in the ITGB3 gene increases the risk for PE in pregnant women with FGR.